PENGARUH MOTIVASI, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN - Agus Budi Purwanto (BBM (Buletin Bisnis & Manajemen), 2016)
This study aims to determine the effect of motivation, compensation and work environment on employee productivity. The research sample was determined by simple random sampling method. Research data collection techniques by spreading questionnaires to employees PT.PELANGI in Demak systematically arranged with multiple choice answers are easy to understand. These samples included 58 people. Test research instruments using validity and reliability. This study uses multiple linear regression model. To get the regression BLUES (best linear Unbiased estimated), previously performed classical assumption. The research proves that there is a positive and significant impact either partially or simultaneously between motivation, compensation and work environment on employee productivity.Keywords: motivation, compensation, work environment, employee productivity